NEW CALIBRATION OF INFRARED MEASUREMENT OF DISSOLVED WATER IN RHYOLITIC GLASSES - Youxue Z.; Belcher R.; Ihinger P.D.; Liping W.; Zhengjiu X.; Newman S. (My University, 1997)
This paper presents a new calibration for infrared analyses of dissolved water and its species concentrations in rhyolitic glasses. The new calibration combines infrared/manometry measurements and infrared study of hydrous rhyolitic glasses heated at different temperatures. The heating experiments show that the ratio of the molar absorptivity of the 5230 cm-1 band to that of the 4520 cm-1 band varies with water concentration. Therefore, earlier calibrations assuming constant molar absorptivities are not accurate. Using our new calibration, total water concentration, and species concentrations can be calculated as follows: (ρ/ρ0)C1 = a0A523, (ρ/ρ0)C2 = (b0 + b1A523 + b2A452)A452, and C = C1 + C2, where C1, C2, and C are the mass fractions of molecular H2O, H2O present as OH, and total H2O, ρ/ρ0 is the ratio of the density of the hydrous glass to that of the anhydrous glass and is approximately 1 - C, A523 and A452 are the absorbances (peak heights) of the 5230 cm-1 and 4520 cm-1 bands per mm sample thickness and relative to a baseline that was fit by a flexicurve, a0 = 0.04217 mm, b0 = 0.04024 mm, b1 = -0.02011 mm2, and b2 = 0.0522 mm2. The new calibration has a high internal reproducibility in calculating H2Ototal, six times better than the calibration of Newman et al. (1986). We expect the new calibration to be accurate in retrieving H2Ototal for H2Ototal =< 5.5 wt% and in retrieving molecular H2O and OH concentrations for H2Ototal =< 2.7 wt%. Using the new calibration, the equilibrium coefficient K for the reaction H2O + O = 2OH is independent of H2Ototal (for H2Ototal =< 2.4 wt%) at a given temperature and can be expressed as lnK = 1.876 - 3110/T, where T is in K. The bulk water diffusivity reported before is not affected by the new calibration, but the molecular H2O diffusivity will be roughly 4-30% greater.